Disclosure of Islamic social reporting on sharia commercial banks in Indonesia - Anis Permatasari; Arie Rachma Putri; Yusvita Nena Arinta (UIN Salatiga, 2021)
This study aims to determine the Disclosure of Islamic Social Reporting at Islamic Industrial Banks in Indonesia with Environmental performance as moderating. The sample in this study changed into 12 Islamic industrial Banks for the 2015-2020 period. The information used is 72 annual reports received by the documentation method. This study use panel data regression and using Moderated Regression Analysis. Results based on the studies found an effect that partially Leverage a company size variable has a positive effect on Islamic Social Reporting, Profitability doesn’t have any significant effect on Islamic Social Reporting. Environmental performance is capable of moderating the connection between company size and Islamic Social Reporting. but, environmental performance isn't always capable of moderating the connection profitability and leverage on the disclosure of Islamic Social Reporting.Keywords: Islamic Social Reporting, Islamic Banks, Profitability, Company Size, environmental performance